Multilayer toroidal tuned liquid column dampers for seismic vibration control of structures. (October 2021) - Ding, Hao; Wang, Jin-Ting; Altay, Okyay; Lu, Li-Qiao
Graphical abstract: Highlights: A multilayer configuration is proposed for the toroidal tuned liquid column dampers. The novel configuration allows to concentrate more damper mass in a limited space. Mathematical description is derived and a design optimization scheme is provided. Real-time hybrid simulations are conducted to investigate the control performance. Efficient multidirectional control capability is observed for a wide frequency range. Abstract: The toroidal tuned liquid column damper (TTLCD) is a recently developed device, which extends the application scenarios of liquid column dampers to multidirectional vibration control. Based on the single-TTLCD, this article creatively designs a multilayer-TTLCD, composed of several cylinder shells and baffles, to improve the damping performance in multidirection. The real-time hybrid simulation (RTHS) technique is employed to experimentally investigate the control efficiency of the multilayer-TTLCD. It is confirmed that the multilayer configuration makes it possible to incorporate more oscillating liquid into the columns of the container without extra occupied floor area, and thus the liquid mass can be raised. Due to the increase of the liquid mass, the multilayer-TTLCD shows certain improvements on peak and root-mean-square (RMS) displacement mitigation over the single-TTLCD when suppressing one specific structural vibration mode. More importantly, it is found that the multilayer-TTLCD is beneficial in multimodal vibration damping and has potential to control multi-order modal responses of structures simultaneously with a wide frequency range.